Extraction Optimization and Qualitative/Quantitative Determination of Bioactive Abietane-Type Diterpenes from Three Salvia Species (Common Sage, Greek Sage and Rosemary) by 1H-qNMR - Panagiotis Kallimanis; Prokopios Magiatis; Angeliki Panagiotopoulou; Kostas Ioannidis; Ioanna Chinou (Molecules, 2024)
The objective of this study was the optimization of the extraction process and the qualitative and quantitative determination of the bioactive metabolites: 12-O-methylcarnosic acid (12MCA), carnosic acid (CA), carnosol (CS), 7-O-methyl-epi-rosmanol (7MER) and rosmanol (RO) in infusions, decoctions, turbulent flow extracts, tinctures and oleolites from three Salvia species: Salvia officinalis L. (common sage, SO), Salvia fruticosa Mill. (Greek sage, SF) and Salvia rosmarinus Spenn (syn Rosmarinus officinalis L.) (rosemary, SR), using Quantitative Proton Nuclear Magnetic Resonance Spectroscopy (1H-qNMR). Regarding the aqueous extracts, decoctions appeared to be richer sources of the studied metabolites than infusions among the three plants. For SR, the turbulent flow extraction under heating was the most efficient one. The optimum time for the preparation of decoctions was found to be 5 min for SF and SO and 15 min for SR. It is noteworthy that SR tinctures were not stable in time due to decomposition of the abietane-type diterpenes CA and CS because of the polar solvent used for their preparation. Contrary to this finding, the oleolites of SR appeared to be very stable. Olive oil as a solvent for extraction was very protective for the contained abietane-type diterpenes. A preliminary stability study on the effect of the storage time of the SF on the abietane-type diterpenes content showed that the total quantity of abietanes decreased by 16.51% and 40.79% after 12 and 36 months, respectively. The results of this investigation also demonstrated that 1H-qNMR is very useful for the analysis of sensitive metabolites, like abietane-type diterpenes, that can be influenced by solvents used in chromatographic analysis.